Screening of Postbiotics against Salmonella and Whole Genome Analysis of the Original Strain - Yan HUANG; Yue SU; Shiyang LI; Xuehe QI; Ai JIA; Yujun JIANG; Xinyan YANG; Chaoxin MAN (Shipin gongye ke-ji)
Objective: To screen postbiotics with exceptional anti-Salmonella activity and develop postbiotic raw materials with industrialization value. Methods: The anti-Salmonella potential of 30 Lactobacillus postbiotic strains was evaluated, focusing on their ability to inhibit the growth of Salmonella enterica serovar Typhimurium (ST). The top five most effective strains were identified, and further assays were conducted to assess their capacity to inhibit ST adhesion and invasion in HT-29 cells. The most significant effective postbiotic was selected for whole genome sequencing and safety evaluation of its originating strain. Results: Lactobacillus plantarum (L. plantarum) JM015 postbiotic exhibited a notable inhibition zone diameter of 15.12±0.53 mm. It effectively reduced the adhesion and invasion of Salmonella to HT-29 cells by more than 90%. Whole genome sequencing of L. plantarum JM015 revealed four bacteriostasis-related gene clusters related to repression: cyclic-lactone-autoinducer, terpene, ribosomally synthesized and post-translationally modified peptide (RiPP)-like, and type III polyketide synthases (PKS). Additionally, it harbors a gene cluster associated with plantaricin production and several genes linked to adhesion, such as fibronectin, glyceraldehyde 3-phosphate dehydrogenase (GAPDH), and triosephosphate isomerase. The safety of the original strain was confirmed through tests for indole production, hemolysis, and nitrate reductase activity. Conclusion: The L. plantarum JM015 postbiotic demonstrates potent anti-Salmonella activity and can as a novel postbiotic ingredient for product development.